Evaluation of integrated teaching among undergraduate medical students: A step towards competency-based medical education. - Dr. Rajesh Gupta; Dr. Sameer Sathe; Dr. Mukesh Pandey; Dr. Abhishek Mehta (Pediatric Review: International Journal of Pediatric Research, 2020)
Background: Didactic lectures are one of the most widely used teaching methods in Indian Medical Colleges.Aim & Objective: To evaluate integrated teaching in medical education assessing existing knowledge of medical students' inappropriate breastfeeding practices.Methodology: This was an observational cross-sectional study. Participants were second phase medical students.Results: A total of 63 students were assessed for the topic with pretest and post-test.Conclusion: Statistically significant absolute learning gain was observed for integrated teaching. Integrated teaching has been appreciated and accepted by undergraduate medical students to improve their learning.